Communicating Climate Change Content in Small and Mid-Sized Museums: Challenges and Opportunities. (3rd July 2021) - Henry, Catherine; Carter, Kate
ABSTRACT: Informal education and outreach can be highly effective at shifting public opinion and action on climate change, particularly in rural areas where climate change may be avoided in regular school curricula. Small and mid-sized museums in more rural areas can serve as important sources of climate change content, even when they are not primarily science museums. However, there are perceived and actual barriers that museums must overcome in order to incorporate this content. In this study, we interviewed staff members of small to mid-sized museums in rural Michigan to learn more about their attitudes and experiences with climate change. We present a summary of common challenges to incorporating climate change in rural museums, along with an overview of how partnerships can overcome these barriers using theory-based science communication approaches.